Las propuestas de integración económica sudamericana: de Diego Portales a Alfredo Palacios (1830-1939) - Lacoste, Pablo (Historia, 1999)
<span style="color: #111111; font-family: ’Trebuchet MS’, ’Lucida Grande’, Lucida, Verdana, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This article analyses various proposals for the economic integration of South America presented both in Chile and Argentina between 1830 and 1930. Their authors here studied include Diego Portales, Juan Bautista Alberdi, Alejandro Bunge, Santiago Marín Vicuña and Alfredo Palacios.